Non‐ASD outcomes at 36 months in siblings at familial risk for autism spectrum disorder (ASD): A baby siblings research consortium (BSRC) study. Issue 1 (15th July 2016) - Charman, Tony; Young, Gregory S.; Brian, Jessica; Carter, Alice; Carver, Leslie J.; Chawarska, Katarzyna; Curtin, Suzanne; Dobkins, Karen; Elsabbagh, Mayada; Georgiades, Stelios; Hertz‐Picciotto, Irva; Hutman, Ted; et al.
Abstract : We characterized developmental outcomes of a large sample of siblings at familial high‐risk of autism spectrum disorder (ASD), who themselves did not have ASD ( n = 859), and low‐risk controls with no family history of ASD ( n = 473). We report outcomes at age 3 years using the Mullen Scales of Early Learning, the Autism Diagnostic Observation Schedule (ADOS), the Autism Diagnostic Interview—Revised (ADI‐R) and adaptive functioning on the Vineland Adaptive Behavior Scales. Around 11% of high‐risk siblings had mild‐to‐moderate levels of developmental delay, a rate higher than the low‐risk controls. The groups did not differ in the proportion of toddlers with mild‐to‐moderate language delay. Thirty percent of high‐risk siblings had elevated scores on the ADOS, double the rate seen in the low‐risk controls. High‐risk siblings also had higher parent reported levels of ASD symptoms on the ADI‐R and lower adaptive functioning on the Vineland. Males were more likely to show higher levels of ASD symptoms and lower levels of developmental ability and adaptive behavior than females across most measures but not mild‐to‐moderate language delay. Lower maternal education was associated with lower developmental and adaptive behavior outcomes. These findings are evidence for early emerging characteristics related to the "broader autism phenotype" (BAP) previously described in older family members of individuals with ASD. There is a need for ongoing clinical monitoring of high‐risk siblings who do not have an ASD by age 3 years, as well as continued follow‐up into school age to determine their developmental and behavioral outcomes. Autism Res 2017, 10: 169–178 . © 2016 International Society for Autism Research, Wiley Periodicals, Inc.